Efficacy and safety of combinations of first‐line topical treatments in chronic plaque psoriasis: a systematic literature review. (20th December 2012) - Hendriks, A.G.M.; Keijsers, R.R.M.C.; de Jong, E.M.G.J.; Seyger, M.M.B.; van de Kerkhof, P.C.M.
Abstract: Background  Most psoriasis patients suffering from mild to moderate disease are treated with first‐line topical treatments, including corticosteroids, vitamin D analogues, topical retinoids and calcineurin inhibitors. Although evidence‐based guidelines on combinations are lacking, the majority of patients will be treated with combinations of these popular topicals at some point during their life‐long treatment. Objectives  We intended to systematically review all available literature on the efficacy and safety of combinations of first‐line topicals in chronic plaque psoriasis, and ultimately, to propose recommendations for combined regimens concerning first‐line treatments. Methods  Databases used as data sources were PubMed, EMBASE and the Cochrane Controlled Clinical Trial Register. According to standardized procedures, literature searches were performed and a level of evidence was determined. Results  In total, 2918 publications on topical combination therapy were revealed, of which 45 articles on first‐line combinations were included. The combination of potent and superpotent corticosteroids with vitamin D analogues provides an improvement of psoriasis within 2 weeks, reaching a maximal improvement after 4 weeks in the majority of patients. The two‐compound product permits once‐daily treatment and therefore is a good solution for chronic plaque psoriasis including scalp psoriasis. Combinations of corticosteroids, with tazarotene or with calcineurin inhibitors do not provide an advantage above corticosteroid monotherapy. Conclusion  The combination of potent corticosteroids with calcipotriol has been studied most extensively and should be regarded as an efficacious and safe treatment option with the two‐compound products as the most practical solution.